Instagram Customer Behavior Pattern Connectivity Based on Customer Path 5A Advocacy in Purchasing Decision Making - Mahnun Mas’adi; Umi Narimawati; Azhar Affandi; Sidik Priadana; Heri Erlangga (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
It is undeniable that one of the causes of changes in consumer behavior in this digital era is the internet and smartphones. Before the advancement of the digital age all activities were carried out manually. For example, before the internet, ticket purchases must come to an agent or station or airport, for shopping daily necessities must come to the store, then return home or to the office, very draining our time. Not a bad thing but wasting time and productivity is not optimal. The internet revolution has been going through generations. Each generation has different behaviors in making purchasing decisions over the internet. Consumer behavior in this generation relies on social media to get information and product reviews. The generation that is very close to the speed of the internet is generation Z, compared to the previous generation. (generation X dan generation Y). According to Stilman Stillman (2018) in (Astuti & Kaligis, 2004, p. 31) It is said that generation Z has figital characteristics that see the real world and the virtual world overlap each other. The information and review is called advocacy in customer path 5A. Customer path 5A itself is a stage of purchasing decisions consisting of (aware, appeal, ask, act, and advocate). The review referred to in this article is the advocate stage, where Instagram customers voluntarily provide recommendations for products and/or brands that have been purchased. Every generation; X, Y and Z, have a relationship in each stage of customer path 5A before making a decision on purchase. The approach in this study uses a literatute review approach.. According (Hariyanti & Wirapraja, 2018, p. 141), Literature review contains reviews, summaries, and thoughts of authors about several library sources (articles, books, slides, information from the internet, image and graph data and others) on the topics discussed.